Does Nature Need Cities? Pollinators Reveal a Role for Cities in Wildlife Conservation - Derby Lewis, Abigail; Bouman, Mark J.; Winter, Alexis M.; Hasle, Aster F.; Stotz, Douglas F.; Johnston, Mark K.; Klinger, Karen R.; Rosenthal, Amy; Czarnecki, Craig A. (Frontiers in Ecology and Evolution, 2019)
We have a small but critical window of time to find strategies that create functional urban landscapes with co-benefits for people and nature. This paper addresses an important question that is fundamental to both urban and landscape-conservation planning: Does nature need cities? The “green infrastructure” focus in urban planning has highlighted cities’ reliance on nature for crucial services—from storing carbon, to keeping cities cooler, to reducing stormwater. Landscape conservation planners increasingly point to urban residents’ need to breathe fresh air, encounter the natural world, and have room to play. But turn the question around: does nature need cities to survive and thrive? The evidence from both urban planning and conservation planning is increasingly “yes.” We explore this evolving view of cities and nature in both the worlds of urban planning and conservation. We argue that the time is ripe to bring these worlds together, and, using our empirical work, establish that cities matter for monarch butterflies, other pollinators and at-risk wildlife species.